2005
DOI: 10.1111/j.1439-0418.2005.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Predatory effect of Coccinella septempunctata on Thrips tabaci and Trialeurodes vaporariorum

Abstract: The predatory effect of adult ladybird Coccinella septempunctata L. on adults of thrips, Thrips tabaci Lindeman, and whiteflies, Trialeurodes vaporariorum (Westwood), was examined in controlled environment chambers, on tomato leaves, in transparent small plastic cages at proportions of 1/(10 + 10), 1/(20 + 20), 1/(30 + 30) and 1/(40 + 40) predator/number of thrips and whiteflies. We conclude that C. septempunctata could be used with success for the biological control of thrips and whiteflies in greenhouse crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Predators' abundance increased with the rise of herbivore prey population on which the carnivore predators live on and prevent the pest population density from reaching the economic injury level (Dixon, 2000).The predator, ladybird Coccinella septempunctata L. condiderably successfully reduced the population richness of thrips, Thripstabaci Lindeman, and whiteflies, Trialeurodes vaporariorum (Westwood) on tomato leaves in controlled environmental condition with predator-prey ratio of1: 30. Besides, the study reported that lady bird beetle' prefer preying T. tabacito T. vaporariorum (Deligeorgidis et al, 2005). The study findings strongly support the present research results of predator-prey responses in mustard field.…”
Section: Species Richness In Jessore Regionsupporting
confidence: 81%
“…Predators' abundance increased with the rise of herbivore prey population on which the carnivore predators live on and prevent the pest population density from reaching the economic injury level (Dixon, 2000).The predator, ladybird Coccinella septempunctata L. condiderably successfully reduced the population richness of thrips, Thripstabaci Lindeman, and whiteflies, Trialeurodes vaporariorum (Westwood) on tomato leaves in controlled environmental condition with predator-prey ratio of1: 30. Besides, the study reported that lady bird beetle' prefer preying T. tabacito T. vaporariorum (Deligeorgidis et al, 2005). The study findings strongly support the present research results of predator-prey responses in mustard field.…”
Section: Species Richness In Jessore Regionsupporting
confidence: 81%
“…Como não foram observados danos de tripes às plantas de melão, conclui-se que o uso de cravo nas bordaduras contribuiu para aumento da diversidade de fitófagos não-praga, que podem servir de alimento alternativo para diversos organismos entomófagos. Os tripes servem como presas para Coccinellidae (Coleoptera), Anthocoridae (Hemiptera) e Chrysopidae (Neuroptera), dentre outros insetos, além de hospedarem parasitóides Eulophidae (LATTIN, 2000;TAGASHIRA e HIROSE, 2001;DELIGEORGIDIS et al, 2005).…”
Section: Resultsunclassified
“…The correlation of low onion thrip damage on leeks with the most ladybirds indicated that beneficial invertebrates may have had a damage limitation effect. Ladybirds are a known predator of onion thrips (Deligeorgidis et al 2005) and there were also significantly more ichneumonid wasps associated with low damage levels. The RDA biplot also showed that there were more lacewings, predators of thrips (Hoddle and Robinson 2004), and hoverflies, more generalist predators, were caught where thrip damage was lowest.…”
Section: Discussionmentioning
confidence: 99%
“…An important predator of thrips are anthocorid bugs (Hemiptera) (Riudavets and Castane 1998) and their use has been advocated for thrip control in glasshouses (Deligeorgidis 2002). Ladybirds (Coccinellidae) and green lacewings (Chrysopidae) are also known to be thrip predators with potential use in biological control (Schade and Sengonca 1998;Hoddle and Robinson 2004;Deligeorgidis et al 2005).…”
Section: Introductionmentioning
confidence: 99%